A simple approach for multi-criteria decision-making on basis of probability theory - Maosheng Zheng; Haipeng Teng; Yi Wang (Engineering Structures and Technologies, 2022)
In the present paper, a new concept of favorable probability is proposed first, and a simplified approach for multi-criteria decision-making is developed on basis of probability theory. It assumes that all the performance indexes of all alternatives can be divided into beneficial and unbeneficial types in the multi-criteria decision-making, and each performance index of all alternative makes its contribution to a partial favorable probability in positively or negatively correlative manners linearly upon its type of beneficial or unbeneficial; the partial favorable probability of each performance index with the same physical meaning is normalized in the alternative group; the product of all partial favorable probability of an alternative makes the total favorable probability of the alternative. As a consequence, all the alternatives can be ranked according to their total favorable probability comparatively in the multi-criteria decision-making. As application examples of the new method, the quantitative assessment of multi-criteria selection for effective dwelling house walls, project managers and contractor for construction works are given in detail, satisfied results are obtained.